Análise do uso de compressive sensing para canal de feedback limitado diante do erro de quantização e ruído em sistemas SM-MIMO - Sá Netto, Raymundo Nogueira de (2012)
Concerning to mobile communications, the information exchange over the channel states between receiving antennas and transmiting antennas is an important tool to enhance the system performance. Thus, in this work, spatially multiplexed MIMO (SM-MIMO) systems with limited Channel State Information (CSI) were analyzed considering two techniques of linear signal detection and pre-equalization Zero Forcing (ZF) and Minimum Mean Square Error (MMSE). Due to this limitation two schemes were considered: Quantization Codebook (QC) e Compressive Sensing (CS). Compressive Sensing is used to generate a reduced CSI feedback to the transmitter in order to reduce feedback load into the system. Therefore, in this work, the performance of the techniques were compared by computational simulations of Bit Error Rate (BER) curves according to the variation of the Signal to Noise Ratio (SNR) for the two considered approaches QC and CS. Furthermore, the presence of quantization error and noise, in the feedback link, were also evaluated for the CS scheme.